The popular election of judges in Mexico: an analysis from a comparative perspective - Kaiceros Barranco, Vladimir; Tovar Plata, Fátima del Rosario (Revista Internacional & Comparada de Derechos Humanos, 2026)
The text analyzes the popular election of judges in Mexico following the 2024 judicial reform, situating it within the debate on judicial independence and democratic legitimacy. It reviews comparative experiences: in the United States, where the vote introduces accountability but also politicization and financial dependence; in Bolivia, where the judicialization of the vote led to illegitimacy and subordination to political power; and in Europe, where judicial councils reinforce professionalization and depoliticization. The paper argues that judicial independence is a guarantee for citizens, not a privilege for judges, and that popular election can lead to judicial populism, undermining impartiality and public trust. In Mexico, the reform runs the risk of replicating negative dynamics if electoral logic is prioritized over judicial careers. The conclusion is clear: true democratization requires an independent, professional, and meritocratic judiciary capable of protecting rights against temporary majorities and political pressures.
Keywords: Judicial election; Popular vote; Comparative perspective; Judicial elections in Mexico